Assessment of serum irisin level in thyroid disorder - Mohamed R Halawa; Mona M Abdelsalam; Bassem M Mostafa; Amira G Ahmed (SpringerOpen, 2018)
Background Irisin is a newly discovered myokin secreted by myocytes responsible for transmission of signals from muscles to other body tissues. Irisin improves systemic metabolism by increasing the energy expenditure. Owing to numerous similarities in action between irisin and thyroid hormones it seems imperative to explore these substances' potential mutual influence on the body. Objective To estimate serum irisin concentration in patients with hypothyroid and hyperthyroid diseases, and to detect the relation of serum irisin in patients with thyroid disorders with creatine kinase (CK), a serum marker of muscle damage. Patients and methods The study comprised 30 hyperthyroid patients (group 1), 30 hypothyroid patients (group 2), and 30 normal persons (group 3). Irisin was measured using enzyme-linked immunosorbent assay. Thyroid-stimulating hormone, triiodothyronine, and free thyroxine levels were measured using chemiluminescent microparticle immunoassay technology. Results Irisin hormone level significantly decreased in hypothyroid patients in comparison with hyperthyroid patients. Irisin hormone level increased in hyperthyroid patients in comparison with normal persons, whereas it decreased in hypothyroid patients in comparison with normal persons. CK level significantly decreased in hyperthyroid patients in comparison with hypothyroid patients. CK level significantly increased in hypothyroid patients in comparison with normal persons, whereas it significantly decreased in hyperthyroid patients in comparison with normal persons. Conclusion Obtained results suggest the influence of thermometabolic state on irisin level.